The Cost Of Being Green: Does Financial Slack Pave The Way For Sustainable Profitability? - Hatiuran, Kezia Agustina; Djazuli, Atim (Jurnal Management Risiko dan Keuangan, 2025)
The inconsistency of empirical findings regarding the impact of ESG on financial performance creates a strategic dilemma for companies, in which sustainability investments may risk suppressing short-term profitability. This study aims to analyze the effect of Environmental, Social, and Governance (ESG) scores on the financial performance of non-financial companies listed in the Kompas 100 Index on the Indonesia Stock Exchange (IDX) during the 2020-2024 period, with financial slack as a moderating variable. A total of 105 observations were obtained from 21 sampled companies and analyzed using panel data regression with the Fixed Effect Model (FEM) and Random Effect Model (REM). The results reveal that the aggregate ESG score has a significant effect on financial performance, as measured by Return on Assets (ROA), while the individual ESG pillars (environmental, social, and governance) do not have a significant impact. Furthermore, financial slack significantly moderates the relationship between the aggregate ESG score and financial performance. These findings suggest that financial flexibility serves as a strategic prerequisite for companies to manage ESG initiatives without compromising short-term performance. This implies the importance of considering internal capacity, alongside ESG scores, in evaluating effective sustainability commitments.